2020
DOI: 10.1109/mci.2019.2954667
|View full text |Cite
|
Sign up to set email alerts
|

How Intense Are You? Predicting Intensities of Emotions and Sentiments using Stacked Ensemble [Application Notes]

Abstract: E motions and sentiments are subjective in nature. They differ on a case-to-case basis. However, predicting only the emotion and sentiment does not always convey complete information. The degree or level of emotions and sentiments often plays a crucial role in understanding the exact feeling within a single class (e.g., 'good' versus 'awesome'). In this paper, we propose a stacked ensemble method for predicting the degree of intensity for emotion and sentiment by combining the outputs obtained from several dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(79 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…The main subtasks of sentiment classification are emotion identification [ 35 ], sentiment intensity prediction [ 36 ], and polarity detection [ 37 ]. Emotion identification detects the emotions behind sentiments such as anger or sadness.…”
Section: Seopinion: Methodologymentioning
confidence: 99%
“…The main subtasks of sentiment classification are emotion identification [ 35 ], sentiment intensity prediction [ 36 ], and polarity detection [ 37 ]. Emotion identification detects the emotions behind sentiments such as anger or sadness.…”
Section: Seopinion: Methodologymentioning
confidence: 99%
“…Dridi, Atzeni and Recupero [ 42 ] proposed a supervised method and found that semantic features and semantic frames can be applied successfully to sentiment analysis within the financial domain, thus leading to better results. Finally, Akhtar, Ekbal and Cambria [ 46 ] proposed a stacked ensemble method for predicting the degree of intensity for emotion and sentiment by combining the outputs obtained from several deep learning and classical feature-based models using a multi-layer perceptron network. To achieve this, Akhtar and colleagues focused on emotion analysis in the generic domain and sentiment analysis in the financial domain.…”
Section: State Of the Artmentioning
confidence: 99%
“…This would not have been possible without the benefits of the unstructured bank of social data. Another recent work [34] attempted to predict the intensities of emotions and sentiments through a stacked ensemble method-namely, convolutional neural networks, gated recurrent units, long-and short-term memory, and support vector regression. The proposed model achieved an impressive result, even compared to other state-of-the-art systems.…”
Section: Previous Workmentioning
confidence: 99%